Approach to hematopoietic cell transplant candidates with respiratory viral detection - Kim, Sara R.; Waghmare, Alpana; Hijano, Diego R. (Frontiers in Pediatrics, 2024)
The management of respiratory viruses prior to hematopoietic cell transplant (HCT) can be controversial and requires special consideration of host factors, HCT parameters, and the specific respiratory virus (RV). In the setting of adenovirus (ADV), human metapneumovirus (HMPV), influenza, parainfluenza virus (PIV), and respiratory syncytial virus (RSV) detection prior to HCT, clinical practice guidelines recommend HCT delay when possible; however, there is much more ambiguity when other respiratory viruses, such as seasonal coronaviruses (CoVs), human rhinovirus (HRV), and SARS-CoV-2, are detected. Our aims for this review include detailing clinical practical guidelines and reviewing current literature on pre-HCT respiratory viral infections (RVIs), including antiviral therapies and prevention strategies, when available. We will center our discussion on three representative clinical scenarios, with the goal of providing practical guidance to clinicians.